FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA ANGGOTA POLISI SATUAN LALU LINTAS POLRES METRO BEKASI KOTA - Nurafian Majid Pranomo; Siswi Jayanti; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
ABSTRACTJob stress is an emotional state that arises because of the mismatch between the level of demand and the ability of individuals. Job stress can occur in any job including working as a police officer who is responsible for maintaining security and public discipline. Indonesia Police Watch (IPW) data shows that dozens of police officers have committed suicide from 2011 to 2016. According to research findings by Police Headquarters, 80% of detective criminal police and traffic police officers experience stress due to workload or work pressure. This research aims to analyze the factors relating to job stress on the traffic unit police officer of Polres Metro Bekasi Kota. The research design used in this research is explanatory research with cross-sectional approach. The population in this research is all members of the police who served in the traffic unit of Polres Metro Bekasi Kota with the total amount 142 people. The sampling technique uses proportional random sampling with sample of 105 people. The research instrument used is a questionnaire. For job stress measurements, the writer uses the GHQ-12, and for statistical analysis, the writer uses chi-square test. The results showed that there was a relationship between career development (p= 0,013) with work stress, where as there was no correlation between age (p=0,176), length of work (p = 0,680), task demand (p=0,242), individual role in organization (p=1,000), occupational relations (p=0,254), and organizational structure and climate (p=0,345) with job stress. The writer recommends providing education and training or dissemination of occupational hazards and counseling to help to prevent and to manage stress, and to create and to socialize transparency of assessment in appointing the head of the unit.